The early history of embodied cognition 1740-1920 the 'Lebenskraft'-debate and radical reality in German science, music, and literature - Hellwarth, Jennifer Wynne 1961- (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2016)
This book evaluates the early history of embodied cognition. It explores for the first time the life-force (Lebenskraft) debate in Germany, which was manifest in philosophical reflection, medical treatise, scientific experimentation, theoretical physics, aesthetic theory, and literary practice esp. 1740-1920. The history of vitalism is considered in the context of contemporary discourses on radical reality (or deep naturalism). We ask how animate matter and cognition arise and are maintained through agent-environment dynamics (Whitehead) or performance (Pickering). This book adopts a nonrepresentational approach to studying perception, action, and cognition, which Anthony Chemero designated radical embodied cognitive science. From early physiology to psychoanalysis, from the microbiome to memetics, appreciation of body and mind as symbiotically interconnected with external reality has steadily increased. Leading critics explore here resonances of body, mind, and environment in medical history (Reil, Hahnemann, Hirschfeld), science (Haller, Goethe, Ritter, Darwin, L. Büchner), musical aesthetics (E.T.A. Hoffmann, Wagner), folklore (Grimm), intersex autobiography (Baer), and stories of crime and aberration (Nordau, Döblin). Science and literature both prove to be continually emergent cultures in the quest for understanding and identity. This book will appeal to intertextual readers curious to know how we come to be who we are and, ultimately, how the Anthropocene came to be